Fotografía en odontología - Vallejo Becerra, Diego (Revista Estomatología, 2000)
The dental picture can constitute a very valuable tool for students, professors as well as for the dentists in general. For example it is good for the illustration of a discovery or a series of observations, documentation of the conditions of "before and later" of a treatment, contribution to the teaching to take registrations and as an assistant in the transmission of knowledge, campaigns in schools or social centers and even as legal protection, because a series of good pictures serves like evidence of the patient's conditions before, during and after the dental treatment. The purpose of the following article is to motivate and to guide the dentist for the obtaining of dental pictures of quality helping to the selection of the required tools as well as of transmitting him some photographic advice to get the required good results.